China's governmentalities [ governing change, changing government - Jeffreys, Elaine , 1960- (Routledge studies on China in transition, 2009)
Contributes to studies of governmentality in non-western and non-liberal settings, by showing how neoliberal discourses on governance, development, education, the environment, community, religion, and sexual health, have been raised in other contexts. This book discusses governmentality to 'other worlds' and the global politics of the present